Phytotherapy of polish migrants in Misiones, Argentina: Legacy and acquired plant species - Kujawska, Monika (2014)
Ethnopharmacological relevance Analyzing how and why phytotherapeutical practices survive a migratory process is important for understanding migrant health seeking behaviour and health demand. Contrary to most studies, which focus on migrants from warm climates who settle in European and American cities, this study explores continuations in the herbal pharmacopoeia of Eastern European peasants who settled down in rural subtropical areas of Argentina. The study also explores the pharmacopoeia among the descendants of the first generation born in Argentina. Material and methods Primary and secondary sources were employed in the study. Data were collected during over 200 interviews (semi-structured, free lists and in-depth) with 94 study participants. Voucher specimens of species mentioned were gathered and identified. Illnesses were reported according to local ethnomedical terminology and classification. Only reports from informants' own experience were included in the analysis. The unit of analysis was a plant use report (plant species×plant part×ailment×informant). The frequency of mentions was calculated for plant parts used and modes of preparation and administration of herbal medicines, and the Informant Diversity Value was also estimated. Secondary information was obtained from ethnobotanical and ethnomedical literature concerning the whole of Poland. A list was made of medicinal plant species known from Poland available in the study area. Then, the similarity between the available species and those used by Polish migrants was evaluated by applying the Simpson index. Results An exhaustive list of 129 plant species used by the Polish community in Misiones, Argentina, was obtained. Among 37 species known form Poland and available in Misiones, 19 were used by the community. There was low consensus on the treatment of health conditions with legacy plants between Polish migrants and the Polish folk pharmacopoeia. The reasons for the relatively low use of legacy species are explained. More continuation has been observed in forms of application and administration of medicinal plants. Most of the continued species are food plants and are predominantly applied as medicinal food. Conclusions In the migratory process, Polish peasants have preserved culturally salient species, which have a wide range of therapeutic applications and are easily accessible. Polish migrants and their descendants have incorporated a great number of local medicinal plant species into their home medicine but at the same time retained traditional ways of administration of herbal medicines. Based on the theory of acculturation, the observed patterns of medicinal plant use in Polish migrant colonies in Misiones indicate good adaptation to the predominant cultural environment. © 2014 Elsevier Ireland Ltd.